Differences in the Effectiveness of Giving Snakehead Fish (Canna Striata) and Catfish (Clariidae) in Healing Prineum Wounds in Postpartum Mothers in the Working Area of ​​the Majalaya Health Center - Dewi, Rosmala; Assyaidah, Sonda Nur (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Perineal tears are a good medium for germs to breed if they don't get proper care. This is also one of the causes of the variation in healing time for perineal wounds. Long wound healing time and inappropriate care techniques can result in postpartum infections. Non-pharmacological therapy that can be given to speed up healing includes the intervention of snakehead fish and catfish therapy. To determine the difference in the effectiveness of providing snakehead fish and catfish therapy in healing perineal wounds in postpartum mothers in the working area of the Majalaya health center. This research is a type of quantitative research. In this research, the Quasy Experiment design method was used with a Pretest and Posttest Nonequivalent Control Group research design. The population in this study was the target postpartum mothers with perineal rupture wounds in the working area of the Majalaya health center who gave birth at the end of June 2024, totaling 30 postpartum mothers. The research sampling technique used total sampling. The samples in this study were postpartum mothers who were in the working area of the Majalaya health center who gave birth with a history of 1st and 2nd degree perineal lacerations in June 2024, 15 postpartum mothers who received snakehead fish therapy intervention and 15 postpartum mothers who received catfish therapy intervention. 15 postpartum mothers. The results of the different tests were carried out using the independent T test on the post-test data for the Snakehead Fish Intervention and Catfish Intervention groups with a p-value = 0.000, which means <0.05. So it can be concluded that there are differences regarding the effect of providing snakehead fish and catfish intervention therapy on the level of healing of perineal wounds in postpartum mothers in the working area of the Majalaya Health Center. There is a significant difference between giving snakehead fish therapy and catfish therapy in healing perineal wounds. Snakehead fish therapy is more effective in healing perineal wounds in postpartum mothers compared to giving catfish therapy (p value 0.00 < 0.05). Keywords: Snakehead Fish Therapy, Catfish Therapy, Perineal Wounds, Postpartum Mothers